Influence of information technology on organization strategy - Mabutho Sibanda; Durrel Ramrathan (Foundations of Management, 2017)
The exponential development of information technology has presented many opportunities to organizations; however, it has also presented several challenges. A key challenge is how do organizations effectively use information technology and incorporate it into their strategies to make full use of its capabilities as an enabler. The fast-changing nature of information technology has resulted in little empirical evidence on how it influences organization strategy. The Strategic Alignment Model was a popular model created to assist organizations to align their information technology and their business strategy; however, the growth of technology may have made this model irrelevant in this age. Therefore, organizations need to determine what factors drive this alignment. Using hermeneutic phenomenology, 12 in-depth interviews were conducted within IBM South Africa to determine real-life drivers that help create this alignment. The themes derived from the interview texts reveal that consumers are becoming more empowered; therefore, organizations need to be more flexible in their business models and strategies. Furthermore, the integration of cross-functional roles in the organization at the management level allow for improved alignment between information technology and strategy as better integrated roles bring a combination of these two elements.
Keywords: 650; information technology; strategy; strategic alignment model; business models; digital; market disruption; phenomenology